OP0182 Angiogenic biomarkers predict the occurrence of digital ulcers in systemic sclerosis. (23rd January 2014) - Avouac, J.; Meune, C.; Kahan, A.; Chiocchia, G.; Allanore, Y.
Abstract : Background: Digital ulcers (DU) are frequent in systemic sclerosis (SSc) and represent a heavy burden because of major impact on quality of life. In addition DU is thought as a clinical parameter of severe vasculopathy that can be associated or predict other vascular lesions. Endothelial injury and perturbed angiogenesis/vasculogenesis are strong contributor to the genesis of DU. Treatment remains a challenge and the identification of reliable predictors of DU is still an unmet clinical need in SSc. Objectives: To evaluate the possible merit of different endothelial markers for the prediction of ischaemic DU. Methods: Endothelial markers were assessed in a prospective cohort of 100 SSc patients without known any cardiovascular involvement or severe comorbidities at presentation. Circulating endothelial progenitor cells (EPCs) and circulating endothelial cells (CECs) were quantified in peripheral blood by flow cytometry after cell sorting, as previously described (1). Serum levels of placenta growth factor (PlGF), soluble vascular adhesion molecule (sVCAM) and vascular endothelial growth factor (VEGF) were measured by quantitative sandwich enzyme-linked immunosorbent assay (ELISA) technique (Quantikine kits, R&D systems). The primary outcome was the occurrence during a planed 3-year follow-up of one or more new ischemic DU, defined by a painful area ≥2mm in diameter with visible depth and loss of dermis localized on fingertips. Results: The mean ± standard deviation (SD) age of the 100 patients (89 women) was 56±13 year old and the mean ± SD disease duration was 9±8 years at baseline. Forty patients had the diffuse cutaneous subset, and 60 the limited. During the planned follow-up, seventeen patients developed new ischaemic DU (8 patients with a history of previous DU and 9 patients with no previous DU). By multivariate analysis focused on biomarkers, high PlGF serum levels (Hazard Ratio, HR: 7.95, 95% confidence interval, CI, 2.09-30.10, p=0.002) and low EPC counts (HR: 2.33, 95% CI 1.44-12.22, p=0.03) were identified as predictors of the occurrence of at least one new DU. Multivariate analysis including these three biomarkers and SSc-related disease characteristics identified high PlGF serum levels (HR: 5.04, 95% CI: 1.19-21.09) and a history of DU (HR: 9.51, 95% CI 1.54-58.77) as independent predictors of new DU. In an alternate model excluding patients with a history DU at baseline, low EPC counts (HR: 7.95, 95% CI 2.09-30.09) and high PlGF serum levels (HR: 13.46, 95% CI 1.58-114.73) were found as predictors of new DU. Conclusions: This study identified low circulating EPC counts and high PlGF serum levels as predictors of new DU in SSc. It highlights the critical role of angiogenesis in this vascular outcome. These markers may improve DU risk stratification and therefore allow earlier therapeutic intervention. References: Avouac J et al, Ann Rheum Dis 2008. Disclosure of Interest: None Declared